Food allergy: immune mechanisms, diagnosis and immunotherapy - Yu, Wong; Freeland, Deborah M. Hussey; Nadeau, Kari C. (Nature reviews. Immunology, 2016)
Key Points There are many forms of food allergy, the most common of which are IgE mediated. Common IgE-mediated food allergies include those to peanuts, tree nuts, cow's milk, egg, soy, wheat, shellfish and fish. The immune system normally develops tolerance to food proteins, at least in part due to the actions of CD4 + regulatory T cells. Food allergy develops when the immune system mounts a T helper 2 (T H 2) cell-mediated response against food epitopes. T H 2 cell sensitization may occur initially at the skin, rather than in the gastrointestinal tract. The early introduction of potentially allergenic foods may prevent the development of food allergies. Patients with established food allergy may become desensitized to food allergens by oral immunotherapy, which is thought to involve a shift from allergen-specific T H 2 cells to CD4 + regulatory T cells, anergic cells and apoptotic cells. Typically, patients must continue regular consumption of food allergen to maintain desensitization. Some desensitized individuals proceed to develop sustained unresponsiveness and no longer require regular ingestion of food allergen to maintain immune system nonresponsiveness. The mechanism and predictors of the transition from desensitization to apparent tolerance are unknown. Research into the immune mechanisms associated with healthy tolerance to common foods, the inflammatory response underlying food allergies, and immunotherapy-induced desensitization promises new approaches to the diagnosis, prevention and treatment of food allergy. Food allergy is a pathological, potentially deadly, immune reaction triggered by normally innocuous food protein antigens. The prevalence of food allergies is rising and the standard of care is not optimal, consisting of food-allergen avoidance and treatment of allergen-induced systemic reactions with adrenaline. Thus, accurate diagnosis, prevention and treatment are pressing needs, research into which has been catalysed by technological advances that are enabling a mechanistic understanding of food allergy at the cellular and molecular levels. We discuss the diagnosis and treatment of IgE-mediated food allergy in the context of the immune mechanisms associated with healthy tolerance to common foods, the inflammatory response underlying most food allergies, and immunotherapy-induced desensitization. We highlight promising research advances, therapeutic innovations and the challenges that remain.